2020
DOI: 10.1002/aenm.202000135
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Enhanced Cycle and Rate Performances of the F‐Substituted P2‐Type Oxide Cathodes for Sodium‐Ion Batteries

Abstract: A series of F‐substituted Na2/3Ni1/3Mn2/3O2−xFx (x = 0, 0.03, 0.05, 0.07) cathode materials have been synthesized and characterized by solid‐state 19F and 23Na NMR, X‐ray photoelectron spectroscopy, and neutron diffraction. The underlying charge compensation mechanism is systematically unraveled by X‐ray absorption spectroscopy and electron energy loss spectroscopy (EELS) techniques, revealing partial reduction from Mn4+ to Mn3+ upon F‐substitution. It is revealed that not only Ni but also Mn participates in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 69 publications
2
93
0
Order By: Relevance
“…into the TM or Na sites and microstructure tailoring have been adopted for modifying P2-Na x TMO 2 . However, to our knowledge, anionic substitution such as O-site F-substitution has rarely been reported for ameliorating the electrochemical performance of P2-Na x TMO 2 to date. , For instance, F-substituted P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 – x F x ( x = 0–0.07) cathodes were designed recently by Dai’s group and they found that F-substitution enables partial reduction of Mn 4+ to Mn 3+ in the pristine state, which hampers the Ni 2+ /Mn 4+ cation ordering, and thus the biphasic reaction during the low voltage region is clearly suppressed. As a consequence, the F-substituted P2-Na 2/3 Ni 1/3 Mn 2/3 O 1.95 F 0.05 shows much improved cycle and rate performance as compared to P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 …”
Section: Introductionmentioning
confidence: 99%
“…into the TM or Na sites and microstructure tailoring have been adopted for modifying P2-Na x TMO 2 . However, to our knowledge, anionic substitution such as O-site F-substitution has rarely been reported for ameliorating the electrochemical performance of P2-Na x TMO 2 to date. , For instance, F-substituted P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 – x F x ( x = 0–0.07) cathodes were designed recently by Dai’s group and they found that F-substitution enables partial reduction of Mn 4+ to Mn 3+ in the pristine state, which hampers the Ni 2+ /Mn 4+ cation ordering, and thus the biphasic reaction during the low voltage region is clearly suppressed. As a consequence, the F-substituted P2-Na 2/3 Ni 1/3 Mn 2/3 O 1.95 F 0.05 shows much improved cycle and rate performance as compared to P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 …”
Section: Introductionmentioning
confidence: 99%
“…The above results signify that the Na storage process in SnO 2 @C@TiO 2 and SnO 2 @C is mainly capacitive controlled. [ 33,34 ]…”
Section: Resultsmentioning
confidence: 99%
“…3a). For P2-NaMNNb, three pairs of redox peaks were found at 3.12/3.2, 3.28/3.34 and 3.56/3.64 V, respectively corresponding to the Ni 2+ /Ni 3+ /Ni 4+ redox couples respectively [14][15][16][17] . It is noted that, Nb doping can efficiently reduce the polarization voltage (ΔV) between adjacent anodic and cathodic peaks is reduced from 97 to 61 mV, which agrees well with the charge/discharge profiles of the P2-NaMNNb and P2-NaMN (Supplementary Fig.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Among the layered structure (mainly P2, O3, according to the count of edge-sharing TMO 6 octahedra with the oxygen piling in ABBA or ABCABC stacking 12 as displayed in Supplementary Fig. 1), P2-Na 2/3 Mn 2/3 Ni 1/3 O 2 , with classic composition has been extensively investigated, which displays a striking specific capacity of 160 mAh g -1 within 2.0-4.5 V based on Ni 2+/3+/4+ redox couples [13][14][15][16][17] . Nevertheless, such a structure suffers from irreversible structural changes or phase transitions (e.g.…”
Section: Introductionmentioning
confidence: 99%